PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUASAN KONSUMEN PADA PT PELAYARAN MEGAH JAYA SEJAHTERA - Devi Febiasputri; Sri Afridola (Jurnal Ilmiah Ekonomi Manajemen: Jurnal Ilmiah Multi Science, 2020)
ABSTRACTThe current business environment is more and more newcomers in dominating the market. Companies must be able to utilize the resources that are facilitated in order to compete with other competitors. Consumers need services that can make them feel satisfied when consumers before traveling and while traveling, problems that often occur in Majestic in Sekupang namely frequent errors in the BMS (Boarding Management System) and Majestic Portal Agent which makes the check-in process disrupted , therefore consumers must wait a long time. The purpose of this study was to determine the quality of service and promotion of customer satisfaction at PT. Pelayaran Megah Jaya Sejahtera. The population in this study amounted to 40,679 consumers who had purchased a Majestic Ferry ticket in Sekupang in January-June 2019. Hypothesis testing with α = 5% obtained calculated F value = 366.765 while F table value = 3.01. So F arithmetic F table, and the probability (sig) of 0,000 0.05. So simultaneously the service quality and promotion variables together have a significant effect on customer satisfaction.Keywords: Service Quality; Promotion; Customer Satisfaction